Răspuns :
Iti scriu direct cu ce e echivalenta fiecare ecuatie si solutiile.
2x+3-6x=-17 ⇔ -4x=-20 ⇒ x=5
2x+2=3x+3 ⇔ -x=1 ⇒ x=-1
2x+2=4-1+2x ⇔ 2=3..hm, fals, sigur ai copiat bine?
2x+3-6x=-17 ⇔ -4x=-20 ⇒ x=5
2x+2=3x+3 ⇔ -x=1 ⇒ x=-1
2x+2=4-1+2x ⇔ 2=3..hm, fals, sigur ai copiat bine?
1) 2x + 3 - 6x = - 17
- 4x = - 17 - 3
- 4x = - 20 , inmultesti cu - 1
4x = 20 ⇒ x = 20/4 ⇒ x = 5
2) 2x + 2 = 3x + 3
2x - 3x = 3 - 2
- x = 1, inmultesti cu - 1
x = - 1
3) 2x + 2 = 4 - 1 + 2x
2x + 2 = 3 + 2x
2x - 2x = 3 - 2
0 = 1, nu convine
- 4x = - 17 - 3
- 4x = - 20 , inmultesti cu - 1
4x = 20 ⇒ x = 20/4 ⇒ x = 5
2) 2x + 2 = 3x + 3
2x - 3x = 3 - 2
- x = 1, inmultesti cu - 1
x = - 1
3) 2x + 2 = 4 - 1 + 2x
2x + 2 = 3 + 2x
2x - 2x = 3 - 2
0 = 1, nu convine